Factors affecting the quality of life among the rural community living along Pahang River and Muar River in Malaysia - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (American-Eurasian Network for Scientific Information, 2011)
The role of rivers in Malaysia in uplifting the socio-economic status of the rural community cannot be denied. With the ability to uplift the socio-economic status of the rural community, it is also expected that their quality of life can also be enhanced. This study intends to reveal the level of quality of life of the rural community living along two major rivers in Malaysia, Pahang River and Muar River and to investigate the factors affecting their quality of life. This is a quantitative study, where data were gained from 900 respondents from three main cities along Pahang River and Muar River namely Pekan, Bahau and Muar. Results gained have proved that the respondents studied have a moderate level of quality of life. However, further analysis have specifically proven that respondents studied have a high level of quality of life in the aspect of social involvement and relationship, home condition, safety at the areas and education. Analyses done have confirmed that there is a significant difference between quality of life and all of the independent variables studied. Using Pearson product-moment, this study managed to identify significant relationships that occur between quality of life and four independent variables studied.